The time course of synaesthetic colour perception. (August 2021) - Lungu, Laura; Rothen, Nicolas; Terhune, Devin B.
Abstract: Grapheme–colour synaesthesia is a neurodevelopmental condition wherein perception of numbers and letters consistently and involuntarily elicits concurrent experiences of colour photisms. Accumulating evidence suggests that heterogeneity in the visuospatial phenomenology of synaesthesia is attributable to the operation of top-down processes underlying photisms experienced as representations in associator synaesthetes and bottom-up processes subserving photisms experienced as spatially localized in projector synaesthetes. An untested corollary of this hypothesis is that bottom-up mechanisms will actuate earlier photism perception in projector than associator synaesthetes. We tested this prediction in a pre-registered study wherein associators and projectors completed adaptive temporal order judgement tasks for graphemes, colours, and photisms. In corroboration of the hypothesis of differential photism access across subtypes, projectors displayed lower photism colour thresholds than associators whereas the two subtypes did not significantly differ in veridical colour thresholds. Synaesthetes did not differ in grapheme or colour thresholds relative to non-synaesthete controls. These results are consistent with the proposal of differential neural mechanisms underlying photism perception in subtypes of grapheme–colour synaesthesia and warrant renewed attention to heterogeneity in the mechanisms and phenomenology of this condition.